2018
DOI: 10.6018/analesps.34.2.290171
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness and psychotic experiences in college students

Abstract: <p>The study of the relation between psychotic experiences and mindfulness in the general population is linked to research into factors of risk and protection against the development of a psychotic disorder. This study looks into the presence of psychotic experiences in a sample of university students and whether there is any variation according to gender. It also analyzes the predictive and discriminant relation of mindfulness with these experiences. The sample consisted of 526 university students (72.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…PEs are common in adolescence, often co-occur with mental disorders [8][9][10][11], and may increase the risk of depression, anxiety, and substance abuse during adolescence [12][13][14], and of psychosis later in life [15]. Some studies have found that PEs are correlated with various factors, such as sex, age, and mental health (depression, stress, and anxiety) [6,16]. College-aged students in particular are at the peak age of onset for mental problems, especially depression and anxiety [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…PEs are common in adolescence, often co-occur with mental disorders [8][9][10][11], and may increase the risk of depression, anxiety, and substance abuse during adolescence [12][13][14], and of psychosis later in life [15]. Some studies have found that PEs are correlated with various factors, such as sex, age, and mental health (depression, stress, and anxiety) [6,16]. College-aged students in particular are at the peak age of onset for mental problems, especially depression and anxiety [17][18][19].…”
Section: Introductionmentioning
confidence: 99%